La implantación del culto imperial de la provincia en Hispania - González Herrero, Marta (Archaeopress Roman archaeology, 2015)
This study shows how the Imperial Cult was introducted and organised in provincial Hispania. The book also examines the collaboration with the Romanised native elites who came from Lusitania, Baetica, and Hispania Citerior.